A Study on the Rationality and Adverse Drug Reactions (ADR) of RHZE Use in Tuberculosis Patients at Dr. Soeselo Regional General Hospital, Tegal Regency - Siti Aisyah (UNIVERSITAS BHAMADA SLAWI, 2026)
The use of anti-tuberculosis drugs (ATDs) requires comprehensive evaluation to ensure the rational therapy and minimize adverse effects that could compromise treatment outcomes. The intensive phase of ATD use is a critical stage because patients are still in the early stages of treatment, making them vulnerable to side effects and therapeutic inaccuracies. This study is a descriptive observational with a cross-sectional design and a prospective approach involving 67 tuberculosis patients in the intensive inpatient phase at Tegal General Hospital from December 2024 to February 2025. Rationality evaluation was based on seven indicators: Accurate diagnosis, Appropriate indication, Appropriate drug selection, Appropriate dosage, Appropriate administration method, Appropriate administration interval, and Vigilance for side effects. Adverse Drug Reactions (ADR) analysis used the Naranjo algorithm. The study results showed that the accuracy of diagnosis, indication, drug selection, administration method, administration interval, and vigilance for side effects reached 100%, while dosage accuracy was recorded at 79.1% with 20.9% being inaccurate. ADR analysis based on the Naranjo algorithm showed 26 cases (38.8%) in the probable category, 32 cases (47.8%) in the possible category, and 9 cases (13.4%) in the doubtful category, with ADR events including nausea (22 patients; 32.8%), red urine (15 patients; 22.4%), headache (8 patients; 11.9%), abdominal pain (7 patients; 10.4%), joint pain (6 patients; 9%), dizziness (5 patients; 7.5%), hepatotoxicity (2 patients; 3%), weakness (1 patient; 1.5%), and loss of appetite (1 patient; 1.5%). An evaluation drug showed that most patients had received rational therapy.